An integrated approach to assessing seismic simulation based on analysis of preseismic, coseismic, postseismic and interseismic creep, and creep damage evolution - Zolochevsky, A.; Thiagarajan, G. (НТУ "ХПИ", 2007)
In this paper, a comprehensive theoretical, numerical and computational investigation based on the analysis of the Parkfield earthquakes will be carried out with the main focus directed at the understanding on how physical and chemical transport phenomena, creep deformation with preseismic, coseismic, postseismic and interseismic periods including steady-state static creep, diffusional creep, cyclic creep and dynamic creep, large strains, tension/compression creep asymmetry, creep dilatancy, active creep damage state (degradation) and passive creep damage state (healing), cyclic variations of velocities in boundary conditions, and tectonic loading history affect fault sliding, seismic activity in the crust surrounding a fault including accelerated seismic release characterized by cumulative Benioff strain, spatiotemporal seismicity patterns, large earthquake cycle on the fault as well as future destructive events. Furthermore, focus is put on how the diffusion, preseismic, coseismic, postseismic and interseismic creep processes, large strains, creep damage evolution including degradation and healing, movement of the front of creep rupture, boundary conditions as well as tectonic loading history may be modeled inorder to understand the workings of the Parkfield earthquakes and to predict new destructive earthquakes within a much shorter time frame than currently possible.

Теоретичні та чисельні дослідження даної роботи направлено на дослідження Parkfield землетрусів. Головні дослідження направлено на пояснення впливу фізичної та хімічної дифузії, деформацій повзучості в досейсмічному, сейсмічному, післясейсмічному та міжсейсмічному періодах,включаючи сталу стадію повзучості, дифузійної повзучості, циклічної та динамічної повзучості, великих деформацій, асиметрії повзучості при розтягу та стисканні, явища ділатансії, активного та пасивного розвитку пошкоджуваності, циклічних варіацій крайових умов, історії тектонічних навантажень, сейсмічної активності земної кори на формування розломів та розривів кори та відповідно на виникнення катастрофічних випадків. Основні дослідження сфокусовано на дослідженні того, як дифузія, досейсмічна, сейсмічна, післясейсмічна та міжсейсмічна повзучість, великі деформації, розвиток процесів пошкоджуваності та заліковування, рух фронту руйнування, крайові умови можуть бути змодельовані для розуміння Parkfield землетрусів та прогнозування нових руйнівних землетрусів.
Keywords: Parkfield землетрусів; дифузія; деформації повзучості; катастрофічні випадки; прогнозування; руйнівні землетруси